A Furniture Ordering System with OTP for Alghail - Al-hubaishi, Hasan Mohammed Hasan Ahmed; Nur Ziadah Harun (Applied Information Technology And Computer Science, 2025)
In today’s digital landscape, where online transactions and systems are ubiquitous, ensuring information security is paramount. The existing manual order management process at Alghail Furniture lacks necessary security measures and operational efficiency, posing critical challenges in the realm of online furniture ordering. To address these issues, this project introduces a Furniture Ordering System for Alghail with a One-Time Password (OTP) verification after registration. This project caters to the domain of e-commerce by implementing a robust OTP verification system during user registration, which introduces dynamic and time-sensitive verification codes. Key security features, including Bcrypt hashing, password validation, Captcha, session time-out, and OTP-based verification, are integrated to fortify the system. The system’s beneficiaries include customers and administrators, providing a secure and user-friendly platform for order placement and account management. The anticipated outcomes encompass heightened security, a more efficient order processing system, and enhanced user experience. The goal is to contribute to a safer and smoother landscape for online furniture shopping, addressing the evolving challenges in the digital realm